2018
DOI: 10.1038/s41467-018-06249-3
|View full text |Cite
|
Sign up to set email alerts
|

Discovering human diabetes-risk gene function with genetics and physiological assays

Abstract: Developing systems to identify the cell type-specific functions regulated by genes linked to type 2 diabetes (T2D) risk could transform our understanding of the genetic basis of this disease. However, in vivo systems for efficiently discovering T2D risk gene functions relevant to human cells are currently lacking. Here we describe powerful interdisciplinary approaches combining Drosophila genetics and physiology with human islet biology to address this fundamental gap in diabetes research. We identify Drosophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 52 publications
9
74
0
Order By: Relevance
“…Recent publication of lenti‐shRNA mediated downregulation of BCL11A (Peiris et al. ) and our current study targeting GCK provide strong support that pseudoislets are effective in the assessment of functional gene down regulation, which requires high efficiency. Moreover, our data indicate that this platform enables future studies to understand the contribution of genes of interest in a model with better preserved first and second phase GSIS.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Recent publication of lenti‐shRNA mediated downregulation of BCL11A (Peiris et al. ) and our current study targeting GCK provide strong support that pseudoislets are effective in the assessment of functional gene down regulation, which requires high efficiency. Moreover, our data indicate that this platform enables future studies to understand the contribution of genes of interest in a model with better preserved first and second phase GSIS.…”
Section: Discussionsupporting
confidence: 70%
“…Reaggregated islet cells form uniformly sized pseudoislets that maintain similar spatial distribution of beta and alpha cells with better first phase GSIS compared with dispersed cells (Hopcroft et al 1985;Halban et al 1987) and original islets (Zuellig et al 2017;Yu et al 2018). Pseudoislets also lend themselves to more efficient gene modification (Caton et al 2003;Arda et al 2016;Peiris et al 2018). Caton et al reported that lentiviral-mediated overexpression of connexin cDNA does not interfere with pseudoislet formation and allows for the transduction of a large proportion of cells (Caton et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we used intracellular sorting with specific antibodies against insulin-, glucagon-and somatostatin-to isolate b-, a-and d-cells, respectively, from fetal or neonatal pancreata ( Supplementary Fig. 1a), like in prior work on human islets 7,17,26 . Quantitative RT-PCR (qRT-PCR; Fig.…”
Section: Pancreas Dissociation and Facs Purification Of Islet Cells Fmentioning
confidence: 99%
“…Humans and pigs are omnivorous mammals with similar physiology and metabolic diseases, including diabetes mellitus and its complications, from diet-induced obesity, insulinopathy and bcell stress [9][10][11] . Recent experimental advances expand possible studies of pig pancreas development to include gain and loss-of-function genetics [12][13][14][15] , fetal surgery and immunomodulation 16 , and primary islet cell genetics 17 . Prior studies of pig pancreas development have largely relied on immunohistological survey of tissue cell types [18][19][20][21] .…”
mentioning
confidence: 99%
“…To establish an approach that would allow manipulation of human islets, we adapted a system where human islets are dispersed into single cells and then reaggregated into pseudoislets (Arda et al, 2016;Furuyama et al, 2019;Hilderink et al, 2015;Peiris et al, 2018; 2018) ( Figure 1A). To optimize the formation and function of human pseudoislets, we investigated two different systems to create pseudoislets, a modified hanging drop system (Foty, 2011;Zuellig et al, 2014) and an ultra-low attachment microwell system.…”
Section: Human Pseudoislets Resemble Native Human Islets and Facilitamentioning
confidence: 99%